Disruption of Glucocorticoid Action on CD11c+ Dendritic Cells Favors the Generation of CD4+ Regulatory T Cells and Improves Fetal Development in Mice - Diao, Lianghui; Hierweger, Alexandra Maximiliane; Wieczorek, Agnes; Arck, Petra Clara; Thiele, Kristin (Frontiers in Immunology, 2021)
A wealth of innate and adaptive immune cells and hormones are involved in mounting tolerance towards the fetus, a key aspect of successful reproduction. We could recently show that the specific cross talk between the pregnancy hormone progesterone and dendritic cells (DCs) is significantly engaged in the generation of CD4+ FoxP3+ regulatory T (Treg) cells while a disruption led to placental alterations and intra-uterine growth restriction. Apart from progesterone, also glucocorticoids affect immune cell functions. However, their functional relevance in the context of pregnancy still needs clarification. We developed a mouse line with a selective knockout of the glucocorticoid receptor (GR) on DCs, utilizing the cre/flox system. Reproductive outcome and maternal immune and endocrine adaptation of Balb/c-mated C57Bl/6 GRflox/floxCD11ccre/wt (mutant) females was assessed on gestation days (gd) 13.5 and 18.5. Balb/c-mated C57Bl/6 GRwt/wtCD11ccre/wt (wt) females served as controls. The number of implantation and fetal loss rate did not differ between groups. However, we identified a significant increase in fetal weight in fetuses from mutant dams. While the frequencies of CD11c+ cells remained largely similar, a decreased expression of co-stimulatory molecules was observed on DCs of mutant females on gd 13.5, along with higher frequencies of CD4+ and CD8+ Treg cells. Histomorphological and gene expression analysis revealed an increased placental volume and an improved functional placental capacity in mice lacking the GR on CD11c+ DCs. In summary, we here demonstrate that the disrupted communication between GCs and DCs favors a tolerant immune microenvironment and improves placental function and fetal development.